Review of Journal of Cardiovascular Magnetic Resonance 2009 - Neubauer S; Mohiaddin RH; Manning WJ; Kilner PJ; Firmin DN; Pennell DJ; Prasad SK (Journal of Cardiovascular Magnetic Resonance, 2010)
Abstract There were 56 articles published in the Journal of Cardiovascular Magnetic Resonance in 2009. The editors were impressed with the high quality of the submissions, of which our acceptance rate was about 40%. In accordance with open-access publishing, the articles go on-line as they are accepted with no collating of the articles into sections or special thematic issues. We have therefore chosen to briefly summarise the papers in this article for quick reference for our readers in broad areas of interest, which we feel will be useful to practitioners of cardiovascular magnetic resonance (CMR). In some cases where it is considered useful, the articles are also put into the wider context with a short narrative and recent CMR references. It has been a privilege to serve as the Editor of the JCMR this past year. I hope that you find the open-access system increases wider reading and citation of your papers, and that you will continue to send your quality manuscripts to JCMR for publication.